ISLAMIC BANKING'S CONTRIBUTION TO ECONOMIC GROWTH IN INDONESIA WITH PROFITABILITY AS AN INTERVENING VARIABLE - Christiana, Dina; Putri, Rizky Nur Ayuningtyas (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
This study was conducted to determine the contribution of Islamic banking to economic growth in Indonesia by using profitability as an intervening variable. Using the nonprobability sampling method in the form of saturated samples, there were 32 samples obtained from Islamic banking financial reports and economic growth reports from 2016-2023. The results of the study indicate that total assets, financing and DPK do not affect the profitability of Islamic banking. NPF has a significant negative effect on the profitability of Islamic banking and FDR has a significant positive effect on the profitability of Islamic banking. Total assets, DPK and profitability do not affect economic growth. Financing has a significant positive effect on economic growth. NPF and FDR have a significant negative effect on economic growth. And profitability is unable to mediate the effect of total assets, financing, NPF, DPK and FDR on economic growth, this reflects that the profitability performance is still low and fluctuating. Challenges in managing banking assets and profitability need to be overcome. Although this study has limitations, this study can still be useful for bank management and be a reference for other researchers. In addition, this study is one of the initial studies that uses profitability to mediate the influence of total assets, financing, NPF, DPK and FDR on economic growth.